In Vitro Effect of Acidic Solutions and Sodium Fluoride on Surface Roughness of Two Types of CAD-CAM Dental Ceramics - Elham Farhadi; Hamid Kermanshah; Shiva Rafizadeh; Reza Saeedi; Ladan Ranjbar Omrani (International Journal of Dentistry)
Objectives. This study assessed the effect of immersion in acidic solutions and sodium fluoride on surface roughness of dental ceramics. Materials and Methods. 40 blocks of Vitablocs Mark II and IPS e.max CAD (5 × 5 × 3) were prepared. The samples were divided into five groups (n = 8) for immersion in artificial saliva (control), artificially prepared gastric acid, acetic acid, 0.02% sodium fluoride + gastric acid, and 0.02% sodium fluoride + acetic acid. The samples were immersed for 168 hours in the respective solutions except for sodium fluoride, in which the samples were immersed for 69 hours. The surface roughness of samples was measured before and after immersion using a profilometer. The surface roughness changes of three specimens of each group were evaluated by scanning electron microscopy (SEM). Data were analyzed using one-way and two-way ANOVA, Tukey’s test, and independent t-test. Results. Significant changes were noted in Ra (P=0.002) and Rq (P<0.0001) in both types of ceramics. The lowest changes in Ra and Rq parameters were seen in artificial saliva and gastric acid and highest changes occurred following immersion in 0.02% sodium fluoride + acetic acid and 0.02% sodium fluoride + gastric acid, respectively. Changes in Rz were also significant following immersion in Vitablocs Mark II (P<0.05). Immersion in 0.02% sodium fluoride + gastric acid and 0.02% sodium fluoride + acetic acid produced a rougher surface on both types of ceramics (SEM). Conclusion. Exposure of Vitablocs Mark II CAD and IPS e.max CAD to 0.02% sodium fluoride + gastric acid and 0.02% sodium fluoride + acetic acid significantly increased their surface roughness, while for Vitablocs Mark II, lager defects were seen on its surface.